Chittaprasadan from the Lens of Ayurvedic Sattvavjay Chikitsa – A Conceptual Comparative Study - Kedar Joshi, Vd Tejaswini; Kale, Sushama; Venugopalkrishnan, Sudarsana (International Research Journal of Ayurveda & Yoga, 2026)
The contemporary world is witnessing an unprecedented escalation in psychosomatic disorders; a phenomenon tightly linked to cognitive instability (Chitta-Vikshepa) and a depletion of underlying mental resilience (Sattva). This cross-disciplinary academic white paper presents a structured conceptual synthesis between two pillars of ancient Indian psychology the contemplative methodology of Chittaprasadana (serenity/ purification of mind) as formalized in Patanjali’s Yoga Sutras, and the clinical paradigm of Sattvavajaya Chikitsa (psychotherapy via cognitive restraint) native to Ayurvedic classical treatises (Brihatrayi).Through a hermeneutic analysis and historical text mapping, this study investigates how the four-fold social-emotional attitudes of Yoga Friendliness (Maitri), Compassion (Karuna), Joy (Mudita), and Equanimity (Upeksha) map directly onto the functional therapeutic objectives of Ayurveda’s non pharmacological mind mastery (Mano Nigraha). Furthermore, qualitative observations from a ten-case pilot study are evaluated to examine changes across distinct psycho-somatic constitutions (Deha-Manasa Prakriti). Ultimately, the study rejects the null hypothesis to prove a profound operational correlation, framing a comprehensive blueprint for preventive public mental health, stress immunity, and integrative mind-body clinical interventions.